LEGAL APPLICATION OF THE OFFENCE OF MURDER AND EUTHANASIA IN NIGERIA (UUM Journal of Legal Studies, 2017)
Abstract: Euthanasia is one of the concepts that stifled debate among academics, lawyers, religious scholars and even politicians. The reason being that it is killing human being although forcompassionate reason, and with voluntary consent of the victim. Opponents of legalizing it, rely on the fear of slippery slope, sacred nature of life and question of inheritance. Despite the aforementioned factors, some countries legalised it while it remains a crime in the majority of other countries including Nigeria. We wrote this paper with the aim of highlighting and reinforcing the prohibition of the practice using Nigerian laws. Doctrinal method was employed to achieve the above objectives. In the process both primary and secondary legal materials were fully considered. The scope of the paper was limited to substantive provisions of both the penal code and the criminal code of Nigeria respectively. The aforementioned laws deal with the offence of murder by conduct or omission. However, there is no mention of the direct act of euthanasia, but from the reading of the laws inference can be drawn relating to withholding and withdrawing medical treatment leading to death. The finding of the paper is that although there is an elaborate provision regarding the prohibition of euthanasia under the criminal code, the law is not so adequate under the penal code and both laws are independent of themselves. Since both laws are applied at different geopolitical zones in Nigeria, the inadequacy of the laws will affect the administration of criminal justice in Nigeria. The paper therefore suggests an amendment to the penal code to fill the gap it has created. Keywords: Euthanasia, Physician assisted suicide, Slippery slope, Murder, Nigeria. Abstrak: Euthanasia telah menimbulkan konflik antara ahli akademik, peguam, tokoh agama dan juga ahli politik. Ini adalah kerana ia mematikan atau membunuh manusia sekalipun dilakukan atas dasar simpati dan dengan persetujuan mangsa. Pihak yang menentang euthanasia berpegang kepada faktor-faktor â€˜slippery slopeâ€™, kesucian nyawa dan isu peninggalan. Walaupun begitu, terdapat negara yang mempraktikkan euthanasia manakala negara yang tidak berbuat demikian adalah kerana mengganggap ia sebagai satu jenayah termasuklah Nigeria. Artikel ini bertujuan untuk membincangkan berkaitan larangan perlaksanaan euthanasia berdasarkan undang-undang yang ada di Nigeria. Kaedah doktrinal digunakan untuk mencapai objektif kajian. Kedua-dua data primer dan sekunder turut digunakan dalam proses ini. Skop kajian pula hanya memfokuskan kepada peruntukan undang-undang ada dalam kanun keseksaan dan kanun jenayah. Undang-undang ini ada kaitan dengan kesalahan membunuh sama ada melalui melakukan sesuatu perbuatan atau ketinggalan. Walaupun tidak dinyatakan secara langsung, tetapi perbuatan menahan dan menarik balik rawatan perubatan yang membawa kepada kematian boleh dianggap sebagai euthanasia. Dapatan kajian menunjukkan bahawa walaupun terdapat peruntukan berhubung larangan terhadap euthanasia di bawah kanun jenayah, tetapi ia tidak mencukupi di bawah kanun keseksaan dan kedua-dua undang-undang ini adalah bebas daripada satu sama lain. Memandangkan kedua-dua undang- undang ini digunakan di zon yang berbeza di Nigeria, kelemahan undang-undang ini akan mempengaruhi pentadbiran keadilan jenayah di Nigeria. Oleh itu, artikel ini mencadangkan pindaan dilakukan kepada kanun jenayah bagi mengatasi masalah ini. Kata Kunci: Euthanasia, â€˜Physician assisted suicideâ€™, â€˜Slippery slopeâ€™, Bunuh, Nigeria.